Board composition and performance in Indian firms: A comparative analysis empirical - Sh. D. Chatterjee (The International Journal of Management Science and Information Technology (IJMSIT), 2011)
This paper attempts to describe the relationship between board composition and performance in Indian firms. Indian firms have been classified into four groups-public sector undertakings (PSUs), stand-alone firms, private business group affiliated firms, and subsidiaries of foreign firms. The paper analyzes the relationship between the study and independent variables, using a multiple regression model. Results indicate that the larger boards are less efective in Indian firms, except in the case of PSUs. Board size is becoming an insignificant variable in determining the performance of Indian PSUs. Surprisingly, board independence is insignificant across all categories in India, as per the results of this study, which calls for detailed studies in this area.
Keywords: 650